Peers To Professors: Exploring The Role Of Students And Faculty In Same-Level Reciprocal Peer Assisted Learning In Family Medicine Clerkship - Sami, Muneeza Aamir; Baig, Lubna Ansari; Iqbal, Saima Perwaiz; Shafi, Riffat; Parveen, Sobia (Journal of Rawalpindi Medical College, 2025)
Objective: Peer-assisted learning (PAL) is teaching by the learners to the learners, a teaching strategy globally integrated into curricula. One particular variant is same-year reciprocal PAL, in which peer tutors and tutees are from the same academic year and alternate teaching roles. However, few studies have examined this specific form of PAL, and both student and faculty perspectives on its efficacy remain largely unexplored. To address this gap, we conducted a qualitative study among fourth-year medical students during their Family Medicine clerkship. Methods: Employing content thematic analysis, we gathered data through in-depth interviews and focus group discussions involving both faculty members and students. Students received training to lead small group discussions, and their perceptions were subsequently collected. Coding of the transcripts was carried out by three researchers independently, with themes agreed upon mutually. COREQ guidelines were followed throughout the planning, implementation, and analysis of this study. Results: The finalized themes included "Enhancement of Teaching Skills," "Conducive Educational Environment," "Operational Issues," and "Recommendations for the Future". Conclusion: Our findings suggest that PAL promotes collaboration among students and enhances knowledge, confidence, time management, teamwork and reflecting skills besides many other. It serves as a valuable supplement to traditional teaching methods, although it cannot replace them entirely. Thorough planning prior to implementation is essential for achieving beneficial long-term outcomes for both students and faculty. Key words: peer groups, medical students, learning, clinical clerkship, teaching methods, undergraduate medical education.